Analog and Digital Signals and Systems - Yarlagadda, R. K. Rao.; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
This is a comprehensive and cohesive presentation of analog and digital signal processing and filtering for electrical engineers. The author covers the principle concepts of analog and digital signals, generalized Fourier series approximations with sinusoidal and non-sinusoidal functions, and analog convolutions and correlations. Signals and linear system interactions, system stability and bandwidths are also discussed. Analysis and design of analog low-pass, high-pass, band-pass, band elimination filters, and delay line filters are discussed using operational amplifiers. Problems associated with nonlinear systems are included. Key features include: Discrete-time Fourier transforms SINC functions to illustrate the generalized Fourier series concepts One consistent notation scheme used throughout the book The author addresses the main concepts of digital signals, convolution, correlation and deconvolution. Digital filter designs using finite and infinite based impulse responses are presented along with their filter structures. Also included is coverage of basic analog communications including AM, FM and multiplexing as well as simple digital modulations. Example problems are presented in detail throughout the book and over 400 end of chapter problems are provided for further study.
Basic Concepts in Signals -- Convolution and Correlation -- Fourier Series -- Fourier Transform Analysis -- Relatives of Fourier Transforms -- Systems and Circuits -- Approximations and Filter Circuits -- Discrete-Time Signals and Their Fourier Transforms -- Discrete Data Systems -- Analog Modulation.
Keywords: Engineering; Computer engineering; Systems engineering; Engineering; Circuits and Systems; Electrical Engineering